1980
DOI: 10.1259/0007-1285-53-629-440
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of ultrasound in the detection of fatty infiltration of the liver

Abstract: The association of high-amplitude echoes returned from the liver in diffuse fatty infiltration has now become well recognized. We report our experience on the accuracy with which ultrasound will detect a fatty liver. A review was made of the liver ultrasound images in patients known to have either histologically normal livers or livers with fatty infiltration. Only two of 40 patients with normal liver biopsies had a brightly reflective echo pattern, but 12 of 20 patients with fatty infiltration showed this pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
11

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(73 citation statements)
references
References 1 publication
2
60
0
11
Order By: Relevance
“…Several studies have assessed the sensitivity and specifi city of ultrasound for detecting LS. In these studies, the sensitivity ranged from 60% to 94% and the specifi city from 84% to 97% [21][22][23][24] . In a sample of 94 Brazilian individuals with elevated ALT, 40% presented LS on ultrasound, and both the BMI and history of diabetes were independently associated with the presence of LS 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the sensitivity and specifi city of ultrasound for detecting LS. In these studies, the sensitivity ranged from 60% to 94% and the specifi city from 84% to 97% [21][22][23][24] . In a sample of 94 Brazilian individuals with elevated ALT, 40% presented LS on ultrasound, and both the BMI and history of diabetes were independently associated with the presence of LS 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Liver ultrasonography (US) although not sensitive enough to assess liver fibrosis or inflammation has a sensitivity of 89% and a specificity of 93% for detecting histological steatosis. [7][8][9][10] In the absence of liver biopsy, presumed NASH is conventionally diagnosed by classical ultrasonographic hepatic appearances together with an elevated serum level of alanine aminotransferase (ALT). 1 The prevalence of ultrasonic fatty liver was 2.6% in 810 normal weight Japanese children aged 4-12 years, 7 and increased to 23 and 53% in obese Japanese and Italian children, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…LS has been recognized by a BLP in 1979 [26]. Some authors consider this pattern as highly correlated with LS [6,7,9,10,12,13], especially if associated with a posterior beam attenuation and/or skip areas [10]. Nevertheless, other authors think that BLP might also indicate liver fibrosis [13,[17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the ability of ultrasound to evaluate the presence and degree of LS remains debatable. In fact, although some authors have shown that the bright liver echo pattern (BLP) is strongly correlated with the diagnosis of hepatic steatosis [6][7][8][9][10][11][12][13], other authors think that this pattern is non-specific because the liver echogenicity on ultrasonography also increases with liver fibrosis [14][15][16][17][18][19][20]. Recently, the simultaneous presence of BLP, posterior attenuation, and/or areas with different patterns of fat infiltration (so-called skip areas) around gallbladder or near the portal vein [21] have been identified as distinctive signs of steatosis involving a number of hepatocytes in a microscopic field [30 % [11].…”
Section: Introductionmentioning
confidence: 99%